Human Resource Planning as a Priority Asset of The Company at the Company PT Nahe Unggul Lestari - Siti Nur Hidayati; Tanti Yanuar Rahmad; Rhian Indradewa; Muhammad Dhafi Iskandar (Syntax Corporation Indonesia, 2023)
Human resource planning is an important process for companies to ensure the availability, skills, and quality of the workforce following the needs of the organization. This research aims to understand how PT Nahe Unggul Lestari identifies and plans for appropriate human resource needs and to evaluate the importance of human resource planning as a key asset that supports the company's success. This research uses a qualitative approach with a case study method. The data in this study will be collected through interviews with company management, the human resources department, and relevant employees. In addition, secondary data such as financial reports and company planning documents will also be taken to support the analysis. The collected data will be analyzed thematically. The results show that human resource planning is one of the important factors that can determine the success of the company. The company PT Nahe Unggul Lestari has realized this and has implemented human resource planning as one of its priority assets. Human resource planning at PT Nahe Unggul Lestari has been carried out systematically and structured and has provided many benefits for the company.